1459 Socio-Cultural Factors Related to Malnutrition in Communities of Central India. (October 2012) - Dwivedi, R; Agrawal, A
Abstract : Background: New WHO child growth standards confirmed that children born anywhere in the world have same growth potential, given the optimum start. Growth is influenced more by nutrition, feeding practices, environment, and healthcare than genetics or ethnicity. Objective: To assess the impact of various socio-cultural factors on nutritional status of children. Setting: Randomly selected Anganwadis, 5 each from 3 randomly selected ICDS (Integrated Child Development Scheme) blocks from total 7 ICDS blocks of Bhopal district. Patients: 400 children between 6 months to 3 years registered at selected Anganwadis. Methods: Data collection using structured questionnaire including information on demography, socioeconomic status, feeding practices, knowledge and beliefs regarding childhood nutrition and utilization of different government-led services. This was supplemented by detailed physical examination and anthropometric assessment. Results: Out of 400 children, 123 (30.75%) were moderately malnourished while 30 (7.5%) were severely malnourished with slight female predominance (53.4 and 54.6% respectively). Low birth weight, higher birth order (≥4), delayed initiation and early interruption of breast-feeding, mixed feeding, bottle-feeding, delayed initiation of complementary feeding; irregular Anganwadi visits and illiteracy of parents were significantly associated with malnutrition. Conclusion: Illiteracy and poor socio-economic status leading to faulty feeding practices are the factors still predominant in developing countries which result in increased incidence of malnutrition in children. However, government-led programmes like ICDS through Anganwadis can help improving both education and nutritional status of mothers as well as children as evidenced by lower incidence of malnutrition in families attending Anganwadis regularly and utilizing nutrition and health care services.